Allogeneic transplantation following non-myeloablative conditioning in renal carcinoma. New evidence of the immune mechanisms responsible for the activity of this form of immunotherapy and the pathogenetic role of endogenous retroviruses - Camillo Porta (Frontiers Media S.A., 2011)
In 2000, the influential New England Journal of Medicine published the first impressive results of the use of allogeneic stem cell transplantation following nonmyeloblative conditioning (the so-called 'mini-allo transplant') in the treatment of patients with advanced kidney cancer...